2021
DOI: 10.1037/xlm0000953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of impoverished information on multisensory integration in judgments of learning.

Abstract: According to the principle of inverse effectiveness (PIE), weaker responses to information in one modality (i.e., unisensory) benefit more from additional information in a second modality (i.e., multisensory; Meredith & Stein, 1986). We suggest that the PIE may also inform whether perceptual fluency affects judgments of learning (JOLs). If JOLs follow the PIE, the differences in JOLs for multisensory and unisensory items should increase as the unisensory study items become harder to perceive. That is, an influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…For example, Thelen et al (2015) reported that semantically congruent and incongruent multisensory gains for auditory recognition memory performance were significantly higher (6.35% vs. −11.15%) than those for visual recognition memory performance (2.35% vs. − 3.9%). For such special auditory memory facilitation, some multisensory memory studies have suggested that less effective auditory stimuli can trigger more multisensory benefits (Matusz et al, 2017; Tatz et al, 2020). Previous multisensory studies reported an inverse effectiveness relationship between visual and auditory signals in which poorly perceptible unisensory signals demonstrated strong multisensory enhancement if presented with another unisensory signal (Meredith & Stein, 1983; Stein, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Thelen et al (2015) reported that semantically congruent and incongruent multisensory gains for auditory recognition memory performance were significantly higher (6.35% vs. −11.15%) than those for visual recognition memory performance (2.35% vs. − 3.9%). For such special auditory memory facilitation, some multisensory memory studies have suggested that less effective auditory stimuli can trigger more multisensory benefits (Matusz et al, 2017; Tatz et al, 2020). Previous multisensory studies reported an inverse effectiveness relationship between visual and auditory signals in which poorly perceptible unisensory signals demonstrated strong multisensory enhancement if presented with another unisensory signal (Meredith & Stein, 1983; Stein, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These effects can be observed in the visual modality with smaller fonts (Rhodes & Castel, 2008;Undorf & Zimdahl, 2019;Yang et al, 2018), hard-to-read cursive writing (Geller et al, 2018;Undorf et al, 2017), blurred (Rosner et al, 2015;Yue et al, 2013) or masked words , words with unprimed letters (Fiacconi et al, 2020) and partially deleted object pictures (Besken, 2016). In the auditory modality, a similar effect is found for quiet words (Frank & Kuhlmann, 2017;Rhodes & Castel, 2009), words that are inter-spliced with silences (Besken & Mullligan, 2014;Susser et al, 2013), or words whose signal-to-noise ratio are decreased (Tatz et al, 2021). Even though this effect has been shown repeatedly with single-word materials, the effects of perceptual disfluencies on naturalistic, multi-modal materials remain less clear.…”
Section: Introductionmentioning
confidence: 87%
“…Each recipe consisted of audio-visual information, in which both types of cues were intact, or cues in one or both modalities were distorted. We hypothesized that the distortion manipulation should reduce JOLs more for distorted than intact materials for both visual and auditory cues if the participants are experiencing difficulties for both modalities to the same extent (Peynircioglu & Tatz, 2019;Tatz et al, 2021;Undorf et al, 2018). Alternatively, one of the cues may become more pronounced, rendering the other cue futile (Besken, 2016;Susser & Mulligan, 2015;Tatz & Peynircioglu, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations